Parker Solar Probe observations of helical structures as boundaries for energetic particles. Issue 2 (17th September 2021) - Pecora, F; Servidio, S; Greco, A; Matthaeus, W H; McComas, D J; Giacalone, J; Joyce, C J; Getachew, T; Cohen, C M S; Leske, R A; Wiedenbeck, M E; McNutt, R L; et al.
ABSTRACT: Energetic particle transport in the interplanetary medium is known to be affected by magnetic structures. It has been demonstrated for solar energetic particles in near-Earth orbit studies, and also for the more energetic cosmic rays. In this paper, we show observational evidence that intensity variations of solar energetic particles can be correlated with the occurrence of helical magnetic flux tubes and their boundaries. The analysis is carried out using data from Parker Solar Probe orbit 5, in the period 2020 May 24 to June 2. We use FIELDS magnetic field data and energetic particle measurements from the Integrated Science Investigation of the Sun (IS⊙IS) suite on the Parker Solar Probe. We identify magnetic flux ropes by employing a real-space evaluation of magnetic helicity, and their potential boundaries using the Partial Variance of Increments method. We find that energetic particles are either confined within or localized outside of helical flux tubes, suggesting that the latter act as transport boundaries for particles, consistent with previously developed viewpoints.